Disclosure requirements, the release of new information and market efficiency: new insights from agent-based models - Oliver Hermsen; Björn-Christopher Witte; Frank Westerhoff (Economics: The Open-Access, Open-Assessment E-Journal, 2010)
We explore how disclosure requirements that regulate the release of new information may affect the dynamics of financial markets. Our analysis is based on three agent-based financial market models that are able to produce realistic financial market dynamics. We discover that the average deviation between market prices and fundamental values increases if new information is released with a delay, while the average price volatility is virtually unaffected by such regulations. Interestingly, the tails of the distribution of returns become fatter if fundamental data is released less continuously, indicating an increase in financial market risk.
Keywords: G14; G18; 330; Agent-based financial market models; market efficiency; release of new information; disclosure requirements; regulation of financial markets; Monte Carlo analysis; Publizitätspflicht; Ankündigungseffekt; Kapitalmarkttheorie; Agent-based Model; Finanzmarkt; Effizienzmarktthese; Kapitalmarktrecht; Theorie